2005
DOI: 10.1038/sj.bjc.6602718
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to tumour challenge after tumour laser thermotherapy is associated with a cellular immune response

Abstract: Previous studies in our laboratory have shown that interstitial laser thermotherapy (ILT) of an experimental liver tumour is superior to surgical excision, at least partly due to a laser-induced immunological effect. The aim of the present study was to investigate the time -response relationship of the ILT-induced immunisation and the cellular response of macrophages and lymphocytes. A dimethylhydrazine-induced adenocarcinoma was transplanted into the liver of syngeneic rats. Rats with tumour were treated 6 -8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Many studies have been performed showing that local ablative therapies induce an inflammatory response [14,15,[23][24][25]. In this study we show that the inflammatory reaction induced by RFA is primarily observed in distant hepatic metastases, but not in perinecrotic Journal of Surgical Oncology Fig.…”
Section: Discussionsupporting
confidence: 54%
“…Many studies have been performed showing that local ablative therapies induce an inflammatory response [14,15,[23][24][25]. In this study we show that the inflammatory reaction induced by RFA is primarily observed in distant hepatic metastases, but not in perinecrotic Journal of Surgical Oncology Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The identification of a population of AFP-specific CD4 ϩ T cells during therapy that are not detectable in treatmentnaive patients could be explained by work showing that necrotic cells induce a different set of class II peptides than cells dying via apoptosis (36). In animal tumor models, an in situ vaccination effect has also been proposed to occur after photodynamic therapy, interstitial laser thermotherapy, and radiofrequency ablation, all of which produce necrosis of tumors (35,37,38). Those studies demonstrated treatment-induced generation of a protective tumor-specific T cell response to tumor rechallenge.…”
Section: Discussionmentioning
confidence: 99%
“…Many of PSs that have been studied so far include, but not limited to porphyrins, porphyrin analogs chlorines, phthalocyanines, indocyanines, and other agents with suitable photophysical properties . On the other hand, PTT uses a photoabsorbing agent to convert light into heat, leading to the thermal ablation of cancer cells . In addition to the direct apoptosis and necrosis by light, phototherapies have been well‐known to elicit antitumor immune responses by producing an acute inflammatory response which ultimately activates the production of proinflammatory cytokines and leukocyte infiltration to regulate TME ( Figure ) .…”
Section: Systematic Effect Of Phototherapies On Antitumor Immune Respmentioning
confidence: 99%